PWE-238 Immunisation practices in patients with IBD—a wake up call. (28th May 2012) - Muhammad, R; Wong, C L Y; Limdi, J K
Abstract : Introduction: Patients with inflammatory bowel disease on immunosuppressant therapy may have an increased risk of opportunistic infections. We reviewed our practice in 150 consecutive patients attending our IBD clinics to see if our practice was in line with recommendations by the European Crohn's and Colitis Organisation and the American College of Gastroenterology. Methods: Patients were considered immunosuppressed if they were on doses of prednisolone >20 mg/day or equivalent for 2 weeks or more, ongoing treatment with effective doses of 6-MP/Azathioprine, Methotrexate, Infliximab and Adalimumab or had these agents discontinued within 3 months. Data were collected from electronic records, clinical case notes and pathology results database review. Up to date and childhood immunisations including previous history of Varicella and Zoster infections was obtained from the primary care physicians. Results: 150 IBD patients (Crohn's disease n=80, Ulcerative colitis n=70) were included; 79 were female. The median age was 51 and median disease follow-up was 23 years. 29 patients (19.3%) were not on any treatment at the time of the audit, 19 (65.5%) out of these 29 patients had therapy with glucocorticoid, thiopurine or biologics previously. 52 patients (34.7%) were on a 5 ASA and 71 patients (47.3%) were on effective immunosuppression as defined above. These included 26 patients on thiopurines (36.6%), 3 on Methotrexate (4.2%), 13 on Infliximab (18.3%), 12 on thiopurines + Infliximab (16.9%), 1 on Methotrexate + Infliximab (1.41%), four patients on Adalimumab (5.6%), 3 on Adalimumab + thiopurines (4.2%), 7 on glucocorticoids alone (9.9%) and 2 on Infliximab + Prednisolone (2.8%). Immunisation history was taken in 29 out of the 150 patients (19.3%). Among the patients on immunosuppressive therapy 29 (40.8%) had chest radiographs performed, 16 (22.5%) were tested for Hepatitis B, 16 (22.5%) for Hepatitis C, 5 (7.0%) for HIV and 4 (5.6%) were tested for varicella titres. Cervical smears were performed in 14 (19.7%) out of 25 women above the age of 25. Of the 71 patients on immunosuppressants, 31 (43.7%) had no screening tests. Immunisation was carried out for influenza in 42 patients (59.1%), 30 (42.3%) for tetanus, 25 (35.2%) for diphtheria, 12 (16.9%) for pneumococcus, 7 (9.9%) for meningococcus, 5 (7.0%) for Hepatitis B, 4 (5.6%) HPV and 11 (15.5%) for MMR. Conclusion: Our current practice was not in line with recent recommendations and probably reflective of experience at other centres. IBD physicians must work in collaboration with primary care providers to ensure appropriate screening and vaccination in this vulnerable group. We have taken appropriate steps to ensure prompt screening of patients through a newly designed proforma. Competing interests: None declared.